Towards Part Lifetime Traceability Using Machined Quick Response Codes. (2016) - Ventura, C.E.H.; Aroca, R.V.; Antonialli, A.Í.S.; Abrão, A.M.; Rubio, J.C. Campos; Câmara, M.A.
Abstract: In recent years, the manufacturing industry has made several efforts aimed at better monitoring of products life-cycle through special markings added during their manufacturing. Such monitoring is becoming increasingly relevant, especially in order to provide reliable product traceability and other associated services that can be available to the manufacturer, to the retailer and to the end consumer. Thus, low-cost and flexible technologies able to carry data of an individual product during its whole life-cycle currently play an important role. Within this context, the popularity, advantages and facilities of using Quick Response (QR) codes motivate the use of this technology in several applications on the manufacturing industry. Aiming to engrave this kind of code in metallic parts without the need of further laser processing or the use of adhesive labels, this work discusses the machining and reading of QR codes in metallic parts. Challenges in machining codes with different sizes and materials, as well as reading them, are investigated.